Theological Evaluation of Non-Christian Rites - Kaniarakath, George (Journal of Dharma, 1980)
Nihal Abeyasingha, A Theological Evaluation of Non-Christian Rites, Bangalore : TheolcgicalPuhlications in India, 1979, pp.250 +xix .